2009
DOI: 10.1590/s0100-39842009000500004
|View full text |Cite
|
Sign up to set email alerts
|

Correlação interobservador das alterações morfológicas das vias biliares em pacientes com esquistossomose mansoni pela colangiorressonância magnética

Abstract: OBJETIVO: Descrever as alterações das vias biliares pela colangiografia por ressonância magnética (CPRM) na esquistossomose hepatoesplênica e avaliar a concordância interobservador da CPRM na detecção de colangiopatia esquistossomótica. MATERIAIS E MÉTODOS: Estudo prospectivo e transversal em 24 pacientes com a forma hepatoesplênica da esquistossomose mansoni e em 6 pacientes sadios, como grupo controle, com avaliação da via biliar pela CPRM. As alterações da via biliar consideradas foram: distorção, afilament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The present issue of Radiologia Brasileira includes an article approaching alterations in the biliary tree in schistosomiasis mansoni evaluated by magnetic resonance cholangiography (5) . The authors concluded that the alterations observed in the biliary tree were, in decreasing order of frequency, distortion, thinning, stenosis, dilatation and irregularity.…”
Section: Editorialmentioning
confidence: 99%
“…The present issue of Radiologia Brasileira includes an article approaching alterations in the biliary tree in schistosomiasis mansoni evaluated by magnetic resonance cholangiography (5) . The authors concluded that the alterations observed in the biliary tree were, in decreasing order of frequency, distortion, thinning, stenosis, dilatation and irregularity.…”
Section: Editorialmentioning
confidence: 99%
“…Approximately 5% to 10% of the infected patients develop the hepatosplenic form of the disease (1) , which may progress with portal hypertension. Fibrosis, the scarring process that follows the inflammatory reaction caused by the presence of the parasites eggs on the walls of portal vessels, secondarily involving the bile ducts (2) , is the anatomical substrate of this severe form of the disease. Differently from other chronic hepatopathies, the hepatic function is in general preserved in schistosomiasis, as no lesions occur in the hepatocyte.…”
Section: Introductionmentioning
confidence: 99%